Thestral incognitus, a new genus and species of Pentatomidae from Chile (Heteroptera: Pentatomidae: Pentatominae: Carpocorini) - Faúndez, Eduardo I.; Rider, David A. (Zootaxa, 2014)
Thestral incognitus, new genus and species of Pentatomidae (Pentatominae: Carpocorini) is described from central Chile. The relationships among this new genus and other South American genera are discussed.  Also, similarities are noted between Thestral and the Australian genus Poecilotoma. Poecilotoma is tentatively placed in the Carpocorini. A key to aid in the recognition of the genera of Chilean Carpocorini is provided.